Slepica - Slapšak, Svetlana (Monitor ISH, 2005)
Slepica: The Blind Female Singer of the Balkans. The paper analyses the role played by slepice, "blind women", in transmitting tradition in the Balkans, primarily through comparison to the Homeric form of oral poetry. The example of Teiresias, who is blinded by Athena or Hera for having seen (and known) the forbidden and is then given prophetic ability by Yeus, provides the starting-point for comparing the characteristics of the ancient mzthology of blindness to the Balkan one. The concept of blindness is gender-related, since blindness, regardless of the sex of the blind person, is associated with the experience and knowledge which is culturally inscribed into the concepts of the female body.
Keywords: slepota; antična mitologija; tradicija; tradition; balkanske študije